Exploring the reality of seafarers’ deaths and injuries and preventive measures from the cases of overwork-related disorders - Yoshikawa, Toru; Iwaasa, Takumi; Takahashi, Masaya (SANGYO EISEIGAKU ZASSHI, 2024)
Objectives: Till date, only few studies have detailed the reality of overwork-related disorders among seafarers. Therefore, in this study, we aimed to evaluate the prevalence of overwork-related disorders among seafarers and assess factors such as patient attributes, diseases diagnosed at the time of determination, workload factors, and other aspects, thereby suggesting relevant preventative measures. Methods: Among all the patients identified with overwork-related disorders from April 2010 to March 2017, 2,280 cases of cerebrovascular and cardiovascular diseases and 3,517 cases of mental disorders were selected. To identify seafarer-related cases, keywords related to seafarers were extracted. Subsequently, 33 cases of cardiovascular disease and 19 cases of mental disorders were obtained. Results: The average age of the patients with cerebrovascular and cardiovascular diseases was 56.7 years; for those with mental disorders, it was 45.2 years. The patients were most commonly engaged in fishing, transportation, and postal services. Most patients were employed in the deck department or were captains. The most common types of vessels were fishing and cargo ships. Among the diseases diagnosed at the time of determination, cerebrovascular diseases accounted for 20 cases (60.6%) and cardiovascular diseases accounted for 13 cases (39.4%), with cerebral and myocardial infarctions being the most frequent conditions. Among mental disorders, “mood disorders” accounted for 7 cases (36.8%), and “neurotic disorders, stress-related disorders, and somatoform disorders” accounted for 12 cases (63.2%), with major depressive episodes, post-traumatic stress disorder, and adjustment disorders being the most common. The most common workload factor for patients with cerebrovascular and cardiovascular diseases was “long-term excessive work”, and among non-workload factors, “long working hours” and “irregular working hours” were prevalent. For mental disorders, 8 cases were attributed to “extreme psychological stress.” Specific events leading to these diseases included “interpersonal relationships”, “experiencing accidents or disasters”, and “work quantity and quality”. Conclusions: Both cerebrovascular and cardiovascular diseases, as well as mental disorders, showed a notable aging trend among seafarers. Thus, measures that consider the characteristics of elderly workers, such as their physical function, are important. Additionally, as seafarers are distributed across various industries and occupations, measures should be specifically tailored to their industry and job type. Our study confirmed that long working hours and irregular working hours were prevalent in both cases. Therefore, there is an urgent need for further efforts to prevent and mitigate overwork-related deaths among seafarers, including organizational support from onshore workplaces and enhancement of medical and operational support using information and communication technology.